The dose-effect relationship of acupuncture on limb dysfunction after acute stroke: a systematic review and meta-analysis - Wang, Xiaoxuan; Xiao, Lu; Xiao, Lingyong; Tian, Chunlei; Liu, Yi; Dai, Xiaoyu (Frontiers in Neurology, 2024)
Objective This study aimed to investigate the relationship between the dose and efficacy of acupuncture in treating limb dysfunction during acute stroke. Methods Studies were searched from seven databases, including PubMed, Embase, Cochrane Library, Chinese National Knowledge Infrastructure (CNKI), Wanfang Data (WF), VIP information database (VIP), and China Biology Medicine Database (CBM). All databases were searched until August 1, 2023 from inception. The risk of bias was assessed using Cochrane Collaboration’s risk of bias tool (RoB2). Meta-analyses were performed using RevMan V.5.4 and Stata 12.0 statistical software. We used Fugl-Meyer Assessment (FMA) to measure recovery of limb dysfunction, NIH Stroke Scale (NIHSS) to measure neurological deficits, and Barthel index, Modified Barthel Index (MBI), and Activities of Daily Living (ADL) to measure activities of daily living. The primary outcome measure is FMA. After examining and integrating the raw data, we performed a meta-analysis using a 3-step process. First, we investigated the dose-related effects of acupuncture at varying doses and determined the optimal dosage for maximum therapeutic benefits. Second, we determined the difference between post-intervention and baseline scores on the outcomes of interest to determine minimal clinically important differences (MCID) to provide evidence for clinical treatment. Third, by combining the results of step 1 and step 2, we made the recommendations employing the Grades of Recommendations, Assessment, Development and Evaluations (GRADE) tool. Results Twenty-six studies containing 1947 participants were included, among which 61.5% of RCTs had a low risk of bias. Through the three-step analysis, the effect in improving limb dysfunction of acute stroke varied across different acupuncture dosages. Regarding the frequency of acupuncture, the results demonstrated a significant improvement in the low (every other day) and moderate-frequency (once a day) groups (low frequency: MD: 9.02, 95%CI: 5.40–12.64, p < 0.00001; moderate frequency: MD: 10.11, 95%CI: 5.05–15.18, p < 0.00001, heterogeneity (p = 0.87), I2 = 0%). For the acupuncture retention time, the results showed no significant difference between the short and medium retention groups (short retention time: MD: 0.05, 95% CI: −0.21–0.31, p = 0.71; medium retention time: MD: −1.16, 95% CI: −2.80–0.48, p = 0.17, heterogeneity (p < 0.00001), I2 = 99%). For the course of acupuncture, the results showed a significant improvement in the short course treatment (less than 2 weeks) group (MD: 14.87, 95% CI: 12.18–17.56, p < 0.00001, heterogeneity (p = 0.45), I2 = 0%). Conclusion Our study demonstrated the effectiveness of different acupuncture dose in improving limb dysfunction. The pooled data suggested that the optimal intervention dose for acupuncture interval time was low (every other day) and moderate frequency (once a day), the optimal intervention dose for needle course time was short course treatment (less than 2 weeks). But we did not find the optimal intervention dose for needle retention time. Future studies of higher quality are needed to confirm this. Systematic Review Registration:https://www.crd.york.ac.uk/PROSPERO/, CRD42023447202.